Pain perception in contact sport athletes: a scoping review - O`Farrell, A.; Sauvé, W.; Bergevin, M.; Cimadoro, G.; Arvisais, D.; Rainville, P.; Pageaux, B. (Sports Medicine, 2022)
Contact sports athletes are regularly facing acute physical pain in part of their sport; however, the literature investigating pain perception in these athletes remains scarce. This scoping review aimed to explore the literature surrounding pain perception in contact sport athletes and to compile and understand how it is studied. The search strategy consisted of using index terms and keywords in the MEDLINE, EMBASE, SPORTDiscus, Web of Science, PsycINFO, CINAHL and ProQuest Dissertations & Theses Global search engines. Results from 11 studies revealed that a mix of team contact sports and combat sports are studied and are included under the umbrella of contact sports. These athletes are being compared with non-athletes as well as athletes from non-contact sports. The cold pressor test and the pain pressure test are the two predominant methods used to investigate physical pain. This review highlights the need to clearly define sports based on contact levels expected in play to better define the types of pain athletes are facing in their practice. Athletes` level of play as well as years of experience should also be more rigorously reported. While contact sport athletes seem to have a higher level of pain tolerance than both active controls and non-contact athletes, the methods of pain testing are not always justified and appropriate in relation to the pain induced during contact sports. Future experimental studies should use pain testing methods relevant to the pain experienced during contact sports and to better justify the rationale for the choice of these methods.